"The other" in Al Mutanabi's Poetry - Rola Khaled Mohammad Ganem (My University, 2010)
This study is important because it discusses an important poet. Although he has always been in the light spots and his works were the subject for many researches till the moment, no one paid the right attention to "the other" in his works. So this study is new and has a new subject despite the huge amount of researches conducted about his work. The research is concerned about" the other's" image in Al Mutanabi's works, and the most important one is" the other I". that's because the "supreme I" is an important feature in Al Mutanabi's works. The research discusses the image of the poets, the Arab's image before Al Mutanabi became famous, and after he became famous and the image of the other foreigner Muslim" Ajami" and non-Muslim. Investigating "the other's " image in Al Mutanabi's poetry, formed a very clear point of view about the image of" the other I"."The distant I", which was strong in Al Mutanabi's works. No land or sky can limit it, it has no boundaries. " The other poet "that Al Mutanabi considered as an enemy who competed him on his living. It , also, formed a point of view about " the praised Arabic other" before Al Mutanabi's fame, he had a traditional image: brave and generous. " the praised Arabic other" after Al Mutanabi's fame, and Saif Al Dawlah Al Hamadani was the perfect example for this "praised Arabic other" after he became famous, so that Al Mutanabi wrote about one third of his collection of poems "Diwan" about him. Al Hamadani had a very bright image because Al Mutanabi's identity unified with Saif Al Dawlah, who was the leading character in his life and works. The non-Muslims foreigner" Ajami" image was also very clear at" the Diwan", the most famous non-Muslim foreigner that Al Mutanabi praised and satirized at the same time was Kafour Al Ikhshidi's character. The character had two images, the first was bright and Al Mutanabi praised him for a purpose, which was to earn and acquire authority and leadership, the second character was gloomy and it was shown up in the satirize poem. He over satirized him when Al Ikhshidi didn't do what Al Mutanabi was looking for. For" the non-Muslim other", Al Mutanabi used "Al Room" , who had existed in the Arab life through the wars between them.

تكتسب هذه الدراسة أهمية خاصة من كونها تناولت شاعراً كبيراً شغل الدارسين قديماً وحديثاً، إلا أن أحداً منهم لم يلتفت إلى صورة الآخر في شعر المتنبي، وبالتالي تعتبر هذه دراسة جديدة في موضوعها على الرغم من الدراسات التي دارت حوله. وقد تناول البحث صورة الآخر في شعر المتنبي, ومن الصور الأهم فيها صورة الآخر الأنا، ذلك أن الأنا المتعالية كانت من أهم الظواهر التي تميز بها شعر المتنبي. وتناول البحث صورة الشعراء. وصورة العربي قبل شهرة المتنبي وبعد شهرته. وصورة الآخر الأعجمي المسلم وغير المسلم. إن تناول صورة الآخر في شعر المتنبي شكّل لدينا فكرة واضحة عن صورة الآخر الأنا، تلك الأنا المغتربة عن الذات، حيث كانت قوية لدى المتنبي فلم تضمها أرض ولم تحدها سماء. وعن الآخر الشاعر الذي نظر إلى المتنبي نظرة عداء، حيث نافسه على لقمة العيش. وشكّل لدينا فكرة عن صورة الآخر العربي الممدوح قبل شهرة المتنبي، فقد كانت صورته تقليدية تمثلت في الشجاعة والكرم، وعن الآخر العربي بعد الشهرة، وكانت شخصية سيف الدولة الحمداني خير مثال لصورة العربي الممدوح بعد الشهرة، حيث قال فيه المتنبي ما يقارب ثلث الديوان، وبدت صورته مشرقة للغاية، ذلك أن ذات المتنبي اتحدت مع ذات سيف الدولة الذي احتل الصدارة في حياته وديوانه. وقد بدت لنا صورة الأعجمي المسلم جلية في الديوان، ومن أبرز الشخصيات الأعجمية المسلمة التي مدحها وهجاها المتنبي في آن واحد شخصية كافور الإخشيدي، حيث ظهرت شخصيته بصورتين الأولى مشرقة، فقد مدحه المتنبي لغاية معينة، ألا وهي التكسب والحصول على الولاية والحكم، والأخرى قاتمة جاءت من خلال قصيدة الهجاء، إذ أغرق المتنبي في هجائه حين تيقن من أنه لم يحقق له مراده. وتناول البحث صورة الآخر الأعجمي غير المسلم، والتي تمثلت في الروم الذين كان لهم حضورهم في حياة العرب من خلال الحروب التي جرت بين العرب وبينهم.
الآخر في شعر المتنبي